2018
DOI: 10.4103/aer.aer_69_17
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and outcomes of postoperative pulmonary complications following abdominal surgery in a South Indian population

Abstract: Background:Postoperative pulmonary complications (PPC) following abdominal surgery are associated with increased morbidity and poorer outcomes. We prospectively examined risk factors associated with the development of PPC in patients undergoing abdominal surgery.Aims:The primary outcome was to determine the association of predefined risk factors in the prediction of PPC after abdominal surgery. Secondary outcomes were evaluation of outcomes of PPC.Setting and Design:This was a prospective study conducted in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…Both PPC and reintubation are associated with increased patient mortality. 52,53 Although both of them showed a downward trend in the HFNO group compared to the control group in the meta-analysis, HFNO failed to affect mortality. Mortality may not be the primary end point of the meta-analysis which may lead to biases and affect the results.…”
Section: Discussionmentioning
confidence: 92%
“…Both PPC and reintubation are associated with increased patient mortality. 52,53 Although both of them showed a downward trend in the HFNO group compared to the control group in the meta-analysis, HFNO failed to affect mortality. Mortality may not be the primary end point of the meta-analysis which may lead to biases and affect the results.…”
Section: Discussionmentioning
confidence: 92%
“…[24] recorded a 28.2% incidence of pulmonary complications, in patients undergoing emergency abdominal surgery. Kumar et al studied one hundred and fifty patients who underwent abdominal surgery, and of these, 16% developed PPCs and the highest incidence occurred in the emergency surgery group too [25]. Verma et al conducted a study of PPCs in patients of emergency abdominal surgeries and found that pre-operative abnormal chest X-ray changes were 3 times more common in the PPCs group as compared to the control group without PPCs [26].…”
Section: Discussionmentioning
confidence: 99%
“…Ameliyat öncesi dönemde hastanın ameliyat ve sonrası dönem için iyi hazırlanması, ameliyat sonrası komplikasyonların önlenmesinde yardımcı olmaktadır [3][4][5] . Özellikle büyük cerrahi girişimlerin (toraks ve batın cerrahisi gibi) sonrasında solunum komplikasyonları %12.5-%54.5 arasında değişen oranlarda görülmekte olup, cerrahi insizyonun diyafragmaya yakın olması durumunda bu oranların arttığı bildirilmektedir [6][7][8][9] . Literatürde torasik ve abdominal cerrahide %42.4 10 , torasik cerrahide %6.2 11 , üst abdominal cerrahide %20 12 oranında solunum komplikasyonlarının görüldüğü bildirilmektedir.…”
Section: Introductionunclassified